OP95 Risk Factors for First Venous Thromboembolism in and around Pregnancy: A Population Based Cohort Study from the United Kingdom. (17th September 2012) - Sultan, A Abdul; Tata, LJ; West, J; Fiaschi, L; Fleming, KM; Nelson-Piercy, C
Abstract : Background: Venous thromboembolism (VTE) remains one of the leading causes of maternal mortality in high income countries. A lack of robust data on women's risk factors for antepartum and postpartum VTE limit potential prevention. There is a need for estimates of absolute risks at population level according to recognised risk factors. Methods: Using a large primary care database, we analysed 376, 154 pregnancies ending in live births or stillbirths from women 15–44 years of age between 1995 and 2009. We assessed the impact of risk factors on the absolute and relative incidence of VTE for antepartum and postpartum periods using Poisson regression. Results: Postpartum, the strongest risk factor was stillbirth (Absolute VTE Rate=2, 444/100, 000 person-years) followed by varicose veins, BMI >30kg/m2, obstetric haemorrhage, preterm delivery, medical co-morbidities (either SLE, IBD, nephrotic syndrome or cancer) and caesarean section (AR=637/100, 000 person-years or higher). BMI >30kg/m2 conferred a substantial increase in postpartum risk (AR=926/100, 000 person-years) but only a modest increase antepartum (AR=109/100, 000 person-years). Women age>35 years, current smokers, and those with acute systemic infections had small relative increases in antepartum and postpartum VTE to those without such risk factors. Conclusion: Antepartum VTE varies modestly by recognised risk factors, yet women with stillbirths, preterm births, obstetric haemorrhage, caesarean section delivery, co-morbidities or BMI >30kg/m2 are most likely to benefit from thromboprophylaxis postnatally. For example, we estimate that up to 17 to 159 annual VTEs could be avoided annually if all women with stillbirth, preterm birth or caesarean section in the UK received appropriate thromboprophylaxis.